Teachers’ Approaches to Creating Active Learning Environments in English Classrooms in MAN 1 Labuhanbatu Utara - Zainuddin; Gumarpi Rahis Pasaribu (Rahis Cendekia Indonesia, 2025)
This study environments in English classrooms at Madrasah Aliyah Negeri (MAN) 1 Labuhanbatu Utara. A qualitative research design was employed to examine teaching practices in their natural classroom contexts. The participants consisted of English teachers selected purposively based on their active involvement in classroom instruction. Data were collected through classroom observations, semi-structured interviews, and document analysis to ensure depth and credibility. The data were analyzed using an interactive model involving data reduction, data display, and conclusion drawing, with triangulation applied to enhance trustworthiness. The findings revealed that teachers implemented student-centered learning as a core approach by engaging students in group work, pair activities, and collaborative tasks. Interactive teaching strategies, including role plays, discussions, presentations, and language games, were found to significantly promote student participation and confidence in using English. Effective classroom management, such as flexible seating arrangements and clear instructional procedures, supported the smooth implementation of active learning activities. In addition, positive teacher–student relationships created a supportive learning atmosphere that encouraged students to participate without fear of making mistakes. Despite challenges related to students’ varying proficiency levels, limited instructional time, and differences in motivation, teachers demonstrated adaptability in modifying tasks and providing additional support. Overall, the study concludes that the creation of active learning environments in EFL classrooms is influenced by pedagogical, managerial, and affective factors. The findings highlight the importance of teacher agency in fostering meaningful and engaging English learning experiences, particularly in madrasah contexts.aimed to explore English teachers’ approaches to creating active learning